Fractionation, physicochemical, and structural characterization of winged bean seed protein fractions with reference to soybean. (29th December 2017) - Makeri, Mohammad Usman; Mohamed, Sabo Abdulkarim; Karim, Roselina; Ramakrishnan, Yogeshini; Muhammad, Kharidah
ABSTRACT: Proteins from defatted flour winged bean seed ( Psophocarpus tetragonolobus ) were sequentially fractionated with reference to soybean seed ( Glycine max ) using distilled water, 25 g/kg sodium chloride solution, 0.1 M NaOH, and 70% alcohol and subjected to physicochemical, functional, and structural analysis. Winged bean seed had globulin (31.94%) and albumin (26.46%), with denaturation temperatures ( T d ) of 92.82 and 82.76°C, and surface hydrophobicities (SHs) of 214.51 and 189.32, respectively, whereas soybean seed had 34.95% globulin and 32.82% albumin, with respective T d of 81.68 and 90.63°C, and SH of 210.80 and 204.66. This indicates that winged bean albumin could perform better at water/oil interface in an oil-in-water emulsion system because of it higher hydrophobicity, although soybean albumin had higher extraction rate. Both legumes' proteins showed comparable gelation when employed for their gelling ability to form three-dimensional network in food systems. Soybean proteins had significantly ( P  < 0.05) higher foaming capacities, but winged bean proteins foams were more stable and soluble over broad pH, good for manufacture of ice cream and protein beverages, respectively. Though β-sheets and β-turns were the major secondary structures of both protein fractions, soybean albumin had significantly ( P  < 0.05) higher β-sheets than winged bean albumin, whereas winged bean globulin and glutelin had higher content of β-sheets than corresponding soybean fractions. The low amounts of β-sheets in the winged bean albumin and soybean globulin could render them more digestible than the corresponding soybean and winged bean protein fractions. Abbreviations: WB: Winged bean; SB: soybean; T d : denaturation temperature; SH: surface hydrophobicity; SH: surface hydrophobicity; W-ALB: winged bean albumin; W-GLO: winged bean globulin; W-GLU: winged bean glutelin; W-PRO: winged bean prolamin; W-ISO: winged bean isolate; S-ALB: soy albumin; S-GLO: soy globulin; S-GLU: glutelin; S-ISO: soy glutelin and S-PRO: soy prolamin.